Marcos desenvolvimentais das funções executivas na infância - Dias, Émille Burity (2019)
This paper deals with executive functions (working memory, inhibitory control and cognitive flexibility) in childhood, and its main objective is to analyze the development of executive functions. This paper was organized in three parts, as follows: 1) Theoretical considerations on the subject; 2) Performance of EFs in age groups; 3) Analysis of the development structure of SFs. One sample consisted of 120 children of both sexes, between 7 and 11 years old, with an average age of 8.96 years (sd = 1.42). Being 47.5% male. As children were divided into five groups, corresponding to their ages, each group with an average of 20 children. The following instruments were used: somiodemographic questionnaire, Raven progressive matrices, cancellation attention test, direct and indirect order digits, five-digit test, trail test and victorious version. SPSS software was used to perform descriptive analyzes (means, standard deviations, frequencies, percentages) and inferential analyzes: Pearson's correlation test, Manova, t-test and dynamic regression. It was also used or Rstudio to perform confirmatory factor analysis. As the main results are displayed as older children and older years present the best rates of executive functions. Being a variable that best explains the performance in executive functions or school year and the capacity of selective attention. Between 7 and 11 years, a bifactorial developmental structure is observed.